A Small State between Two Major Powers: Nepal’s Foreign Policy Since 1816 - Adhikari, Dhruba Raj (Journal of International Affairs, 2018)
Nepal is a small state situated in a geo-strategic location between two major powers—China and India, the former being a great state, and the latter a middle state. Nepal has asymmetric relations with both India and China in terms of national power. Nepalese psyche has been shaped by the very geostrategic situation since the time immemorial. However, Nepal as a modern state was born only in 1768, since then it has adopted different strategies for its survival according to the changes in international, regional and domestic power equations. During the initial phase (1768-1814), Nepal was called Gorkha empire and it had pursued a grand strategy of sub-regional hegemony while being mindful of the sensibilities of the big powers in the North and the South. Nepal made a transition from imperial grand strategy to small power diplomacy in 1816 when it was defeated in Anglo-Nepal War (1814-16). From 1848, when Jung Bahadur came to power, Nepal started to fully bandwagon with the British colonialists in India. After that, Nepal had followed strategies of ‘special relationship’ with its neighbors, non-alignment, balancing, balking, neutrality, equidistance, equiproximity and trilateral cooperation depending upon changes in domestic, and regional as well as international politics.